Pengenalan Dasar-Dasar Akuntansi dalam Rangka Peningkatan & Memperluas Wawasan Terkait Akuntansi - Thomas Averio (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
This activity aims to provide broader knowledge, understanding and insight to young people, especially students and employees related to accounting. This activity aims to enable participants to understand the definition of accounting, the history of accounting, the purpose of accounting itself, and have a good understanding of the contents of financial statements so that this knowledge can become a provision in the future when these young people enter the world of work or the world of investment or even become an expert in accounting later. This activity is carried out online through the Google Meet application. The target of this activity is young people aged 17 to 20 years who are in Pontianak, West Kalimantan. The number of participants in this activity was 66 participants. This activity took place on Saturday, March 4 2023 and went very well due to good cooperation and coordination from the various parties involved. This activity is expected to be able to contribute and have a positive impact on increasing the knowledge and understanding of participants regarding accounting and can provide broader views and insights for participants